European rules in the field of competition guarantee for the effective functioning of the internal market in the European Union - Valcheva, Alexandra (Law Journal of New Bulgarian University, 2022)
For decades, the European Union has made great efforts to achieve one of its main objectives, namely to build a single internal market in which to ensure the free movement of goods, services, capital and people. To this end, the Union has adopted a number of primary and secondary acts setting out the rules governing the functioning of the internal market and has established various mechanisms to monitor their proper application. Undoubtedly, the completion of the single internal market is one of the most valuable achievements of the European Union, which has led to a number of positive consequences. The main ones are the economic growth and stability of the European Union, the better competitiveness on the international markets, the provision of higher consumer protection, the creation of a more favorable environment for the activities of the enterprises, the liberalization of the different types of services. The basic principles and rules in the field of competition are important for the proper functioning of the internal market, for the development of the economy of the European Union and for the protection of legal entities. These rules constitute antitrust and anti-cartel legislation, merger control, state aid and public enterprises and services. These rules are set out in the founding treaties, in the Charter of Fundamental Rights of the European Union, and in a number of regulations and directives. This article will present an analysis of the basic rules and principles in the field of competition and their impact on the internal market, as well as the relevant jurisprudence of the Court of Justice of the European Union.